G2 Bézier-Like Cubic as the S-Transition and C-Spiral Curves and Its Application in Designing a Spur Gear Tooth - Yahaya, Saifudin Hafiz; Sihombing, Haeryip; Yaakob, Mohd Yuhazri (INSInet Publications, 2013)
Many of the researchers or designers are mostly used the involute curves (known as one of the approximation curves) to design the profile of gears. This study intends to develop the transition (S transition and C spiral) curves using Bézier–like cubic curve function with G2 (curvature) continuity as the degree of smoothness. Method of designing the transition curves is adapted by using circle to circle templates. While the transition curves are completely finished, it will be applied in redesigning the profile of spur gear. The mathematical proofs and simple models are also shown.